Diagnóstico sobre o gerenciamento de resíduos sólidos urbanos no município de Maxixe, Inhambane/Moçambique - Fernando, Agostinho (2013)
The aim of this work is to present a diagnosis on the solid waste management in council of Maxixe, province of Inhambane in Mozambique which is located in southeast of Africa. The preparation of this work consisted of literature review of several authors who pore over municipal solid waste at international level, particularly in Mozambique. The fieldwork was conducted in Maxixe between the months of December 2011 to March 2012, which consisted of data collection on the steps of solid waste management. The interviews were conducted with employees of council, particularly in the sector of urban cleaning, accounting and aldermen. One hundred questionnaires were also applied to householders, to evaluate the cleanliness of the urban municipality. SIG Arcview GIS 9.2 software was applied for the production of maps. The results of the survey indicate that solid waste in the city of Maxixe are characterized by highest percentage of waste consisting of 47.7% organic matter, poor coverage of waste collection, which covers 48% of the total population in three districts and improper treatment and disposal of waste. The results of the survey show that 44% of respondents said that the urban cleaning services are bad, 13% and 2% said are good and excellent, respectively. The urban sanitation sector has no plan for solid waste and other specific plans that could guide the municipality in planning their actions on municipal. To improve the current scenario of solid waste management, it is recommended that the council develop a plan for waste management with householders and greater involvement of the private sector and allocate more financial resources in this area which can reduce the environmental impacts and improve the health of the population.